2014
DOI: 10.3892/mmr.2014.2206
|View full text |Cite
|
Sign up to set email alerts
|

Sanguinarine protects against pressure overload-induced cardiac remodeling via inhibition of nuclear factor-κB activation

Abstract: Abstract. Cardiac remodeling is a major determinant of heart failure characterized by cardiac hypertrophy and fibrosis. Sanguinarine exerts widespread pharmacological effects, including antitumor and anti-inflammatory responses. In the present study, the effect of sanguinarine on cardiac hypertrophy, fibrosis and heart function was determined using the model induced by aortic banding (AB) in mice. AB surgery and sham surgery were performed on male wild-type C57 mice, aged 8-10 weeks, with or without administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…A previous study has verified that the expression of PPAR‐γ can suppress cardiac fibrosis‐mediated cardiac remodeling by inhibiting TGF‐β1 expression . NFκB is found in almost all cell types and can be activated by proinflammatory cytokines and endotoxins, and then translocated to the nucleus to regulate inducible gene expression under both physiological and pathological conditions . Our study has found that the expression of PPAR‐γ can suppress NFκB nucleus translocation and further inhibit inflammatory factor expression and myocardial injury.…”
Section: Discussionsupporting
confidence: 74%
“…A previous study has verified that the expression of PPAR‐γ can suppress cardiac fibrosis‐mediated cardiac remodeling by inhibiting TGF‐β1 expression . NFκB is found in almost all cell types and can be activated by proinflammatory cytokines and endotoxins, and then translocated to the nucleus to regulate inducible gene expression under both physiological and pathological conditions . Our study has found that the expression of PPAR‐γ can suppress NFκB nucleus translocation and further inhibit inflammatory factor expression and myocardial injury.…”
Section: Discussionsupporting
confidence: 74%
“…1) affecting different molecular targets were investigated concerning their effects on cell migration using an in vitro wound healing assay, followed by the study of their interactions with microtubules in GFP co-expressing U2OS cells. These secondary metabolites include 1) sanguinarine, a benzophenanthridine alkaloid from Sanguinaria canadensis that has anti-infection, anti-heart-failure, anti-inflammatory and anti-cancer effects via DNA intercalation and suppression of NF- K B activation [2326]; 2) chelerythrine, a benzophenanthridine alkaloid from Chelidonium majus that inhibits the proliferation of neoplasms and reproduction of bacteria via DNA intercalation and inhibition of protein kinase C [27, 28]; 3) chelidonine, a benzophenanthridine alkaloid from Chelidonium majus that exhibits anti-inflammatory and anti-tumor activities via inhibition of telomerase and tubulin [29, 30]; 4) homoharringtonine, a cephalotaxine alkaloid from Cephalotaxus harringtonia that has been approved by FDA for the treatment of chronic myeloid leukemia via inhibition of protein synthesis [31, 32]; 5) doxorubicin, an anthracycline antibiotic from Streptomyces peucetius that has been commonly used in cancer therapy such as solid tumors, leukemia, lymphomas, breast, lung, ovarian, gastric and liver cancers for more than 40 years via inhibition of topoisomerase II [33, 34]. Microtubule-binding natural products such as paclitaxel, vinblastine, colchicine (an alkaloid from Colchicum autumnale that used for Familial Mediterranean fever and acute gout flares [35]) and podophyllotoxin (a lignan from Podophyllum hexandrum that used to treat Genital warts [36]) were investigated as positive controls.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that SG can exhibit anti-inflammation effects through inhibiting p38 MAPK, consistent with previous findings. 8 …”
Section: Discussionmentioning
confidence: 99%
“…6 , 7 Recent evidence suggests that SG inhibits the occurrence and development of inflammation via the inhibition of the phosphorylation of p38 MAPK and the activation of NF-κB. 8 However, there are few reports about the effect of SG on NP.…”
Section: Introductionmentioning
confidence: 99%